PEMBANGKIT LISTRIK SISTEM HIBRIDA SEL SURYA DENGAN ENERGI ANGIN - Effendi, Asnal; Dewi, Arfita Yuana (Situs resmi ITP Press, 2016)
System power generation of hibrida, surya cell and wind energy are represent power generation combined of two energy potency. The combining from source of this energy aim to be excess and insuffiency at each system earn each other with other system utilize to get more energy, efficiently and effective.